1995
DOI: 10.1056/nejm199512073332305
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Bone Marrow Transplantation as Compared with Salvage Chemotherapy in Relapses of Chemotherapy-Sensitive Non-Hodgkin's Lymphoma

Abstract: As compared with conventional chemotherapy, treatment with high-dose chemotherapy and autologous bone marrow transplantation increases event-free and overall survival in patients with chemotherapy-sensitive non-Hodgkin's lymphoma in relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
1,280
2
45

Year Published

1997
1997
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,241 publications
(1,386 citation statements)
references
References 30 publications
32
1,280
2
45
Order By: Relevance
“…[1][2][3] For such patients treated in this way a 5-year progression-free survival of approximately 50 and 46% can be expected. Individuals who relapse after highdose therapy, however, have a poor outlook due to a combination of disease chemoresistance, cumulative nonhaematological toxicity from previous therapy and sensitivity to further myelosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] For such patients treated in this way a 5-year progression-free survival of approximately 50 and 46% can be expected. Individuals who relapse after highdose therapy, however, have a poor outlook due to a combination of disease chemoresistance, cumulative nonhaematological toxicity from previous therapy and sensitivity to further myelosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these improvements in treatment, approximately 50% of patients with advanced disease will relapse or fail treatment with first line chemotherapy (Fisher et al, 1994;Canellos and Niedzwiecki, 2002;Coiffier et al, 2002). However, salvage chemotherapy followed by high-dose chemotherapy and autologous stem cell transplant (ASCT) in patients with chemo-sensitive HL and aggressive NHL can lead to long-term remission in 46 -55% of patients (Linch et al, 1993;Philip et al, 1995;Schmitz et al, 2002).…”
mentioning
confidence: 99%
“…In 'aggressive' lymphoma, the benefit of such an approach has been demonstrated to be superior to conventional salvage chemotherapy in patients with relapsed disease (Philip et al, 1995) and has an accepted role in those patients whose disease is primary refractory to conventional therapy (Vose et al, 1993;Shipp et al, 1999). In follicular lymphoma, long-term freedom from recurrence may be achieved in those with recurrent disease (Freedman et al, 1999;Apostolidis et al, 2000;Hunault-Berger et al, 2002), and indeed in a randomized study an advantage in both PFS and OS was demonstrated (Schouten et al, 2003).…”
Section: Incorporation Of Rit Into Myeloablative Regimens With Progenmentioning
confidence: 99%